2004
DOI: 10.1038/sj.ijir.3901160
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral ketoconazole to prevent postoperative erections following penile surgery

Abstract: Analgesics and topical agents ineffectively inhibit painful erections after penile and urethral surgery. Oral ketoconazole reversibly inhibits testosterone production and has been used empirically at our institution to decrease postoperative erections. We performed a retrospective review of 38 patients who had undergone penile and urethral reconstructive surgery. In all, 31 patients received 400 mg of ketoconazole three times daily for 10-14 days postoperatively (the study group) and seven patients did not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Ketoconazole and Itraconazole , as 14-α demethylase (CYP51A1) inhibitors, are synthetic antifungal drugs [23] and could be used to treat refractory bone pain and neurologic injury in patients with advanced metastatic prostate cancer [26], [27]. In this study, both drugs were identified to bind to ERα and ERβ with IC 50 or EC 50 value less than 1 µM (Figure 5).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ketoconazole and Itraconazole , as 14-α demethylase (CYP51A1) inhibitors, are synthetic antifungal drugs [23] and could be used to treat refractory bone pain and neurologic injury in patients with advanced metastatic prostate cancer [26], [27]. In this study, both drugs were identified to bind to ERα and ERβ with IC 50 or EC 50 value less than 1 µM (Figure 5).…”
Section: Discussionmentioning
confidence: 89%
“…For example, ketoconazole inhibits the production of testosterone, and has been used by urologists to treat refractory bone pain and impending neurologic injury in patients with advanced metastatic prostate cancer [26], [27], but the molecular mechanism is unknown. In this study, ketoconazole was found to selectively inhibit ERβ with IC 50 value of 0.79 µM and showed good antiproliferative activity on human MDA-MB-231 breast cancer cell line with IC 50 value of 8.95 µM, which indicated that ketoconazole may have more broad-spectrum anti-cancer indications with therapeutic effects of breast cancer in clinic.…”
Section: Resultsmentioning
confidence: 99%
“…41 In addition to its antifungal action, ketoconazole has a resultant side effect that creates a reduction in testosterone levels which has been observed in the treatment of metastatic prostate cancer, preventing postoperative erections and various other medical conditions. [41][42][43] This decrease in testosterone is the reasoning behind the use of ketoconazole in the treatment of recurrent priapism. All patients receiving ketoconazole should be monitored by a physician and given daily prednisone due to ketoconazole's blocking action on the production of adrenal steroids.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…-Cetoconazol, por seu efeito antiandrogênico moderado 44,45 . Todos os casos relatados na literatura são de uso pós-operatório a curto prazo após cirurgia peniana em pacientes sem doença hematológica, e há algumas preocupações teóricas em relação à indução de resistência com o uso prolongado de uma droga antifúngica.…”
Section: Tratamentounclassified